Validation of the name Artemisia anomala S. Moore var. acuminatissima Y. R. Ling (Asteraceae) (Bangladesh Journal of Plant Taxonomy, 2011)
Not available.Keywords: Artemisia; Asteraceae; Nomenclature; Validation.DOI: http://dx.doi.org/10.3329/bjpt.v18i2.9307Bangladesh J. Plant Taxon. 18(2): 203-204, 2011 (December)